Penerapan Etika Bisnis Guna Meningkatkan Kinerja Karyawan Yang Berkualitas Di PT. Nesia Pan Pacific - Hartanto Hartanto; Rizal Rifa’i; Margaretha Agnes Retnowati; Metha probosari; Fitri Nur Kholifah; Aris Prio Agus Santoso (Journal of Creative Student Research, 2023)
Business ethics plays a key role in building strong, competitive companies through strategic planning, good organization, transparency in procedural systems, and a corporate culture supported by good and consistent ethics. This research was conducted using the direct observation method. With a sampling technique collected through interviews with several employees at PT. Nesia pan pacific clothing The results of this research show that good business ethics can improve the quality of employee work by creating a positive work environment and providing motivation. Ethical business practices include transparency, fairness, and social responsibility, which can create a sense of employee trust and loyalty. This can motivate them to work more efficiently and contribute positively to the overall quality of work.